Improving compliance with venous thromboembolism prophylaxis guidelines in obese inpatients. Issue 9 (13th September 2022) - Chee, Adrian; Bortz, Hadley; Yip, Jarrod; McFadyen, James D.
Abstract: Obesity is a well‐recognised risk factor for venous thromboembolism, and increased dosing of pharmacological prophylaxis is recommended in obese inpatients. We performed a clinical decision support intervention by adjusting order sentences of prophylactic enoxaparin within our electronic medical records, which significantly improved appropriate dosing for thromboprophylaxis in obese inpatients at our institution.